2010
DOI: 10.1007/s10661-010-1411-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial water quality assessment of Langat River Basin (Malaysia) using environmetric techniques

Abstract: This study investigates the spatial water quality pattern of seven stations located along the main Langat River. Environmetric methods, namely, the hierarchical agglomerative cluster analysis (HACA), the discriminant analysis (DA), the principal component analysis (PCA), and the factor analysis (FA), were used to study the spatial variations of the most significant water quality variables and to determine the origin of pollution sources. Twenty-three water quality parameters were initially selected and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
208
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(216 citation statements)
references
References 40 publications
4
208
0
4
Order By: Relevance
“…During the study, pH value in the river water was 6.37, which is within the permissible limit stated by MOH (6.50 to 9.0). According to [3], the pH of river water is near to neutral because the downstream area of Langat River has high level of exposure to seawater. Thus the pH value tend to increase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the study, pH value in the river water was 6.37, which is within the permissible limit stated by MOH (6.50 to 9.0). According to [3], the pH of river water is near to neutral because the downstream area of Langat River has high level of exposure to seawater. Thus the pH value tend to increase.…”
Section: Resultsmentioning
confidence: 99%
“…State water authorities are responsible for monitoring water intake by treatment plants. River water quality is measured based on a water quality index (WQI), which is built from six selected parameters, namely, dissolved oxygen (DO), BOD 5 , COD, SS, NH 3 -N, and pH. According to the latest Environmental Quality Report issued by Malaysia's DOE, 34% and 7% of the 473 rivers monitored are slightly polluted and polluted, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sources of the Langat River pollution are identified as industrial discharge (58%), domestic sewage from treatment plants (28%), construction projects (12%) and pig farming (2%) [6]. A study from a research showed that major sources of surface water quality variations in Langat River come from industrial effluents, wastewater treatment plants, domestic and commercial areas [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, 42% of the rivers systems have been classified as polluted, mostly due to surface runoff, discharge of sewage and industrial effluent [2]. As the human population increases, the pressure on the utilization of natural resources increases in tandem.…”
Section: Introductionmentioning
confidence: 99%